Islamic Universities towards Knowledge-Based Society - Wahyudin Noor; Moh. In'ami; Masrukhin Masrukhin (ADDIN, 2022)
The phenomenon related to foreign workers entering the country; seems to be unstoppable anymore. On the other hand, the rapid rapidness of breakthroughs in information technology, consciously or unconsciously, has formed new social moral attitudes and knowledge for human individuals. In response to this, people often experience cultural shock. University also, as an institution that is required to be able to translate the situation almost stuttering. Some of them were forced to close and no longer operate. This study is qualitative with a phenomenological approach using the literature review method. Field data was obtained from various books and other documents. Finally, the researcher synthesizes various existing data and then makes an interpretation (analysis) so that this research produces a comprehensive and accurate result. The study results explain, Islamic universities as an entity can develop a Knowledge-Based Society. Through production activities, dissemination, and effective utilization of knowledge, of course, there will be an increase in aspects of social development, even economics. Building a Knowledge-Based Society is not a light problem, but it is necessary to implement groundbreaking policies, for example, completing the dichotomy of science, strengthening academic culture, strengthening various research institutions, preparing knowledge workers and cooperation.